Signifikansi Peristiwa Malari 74: Mahasiswa dalam Lanskap Politik Indonesia - Donny Maulana; Hariyono Hariyono; Indah Wahyu Puji Utami; Aditya Nugraha Widiadi; Arif Subekti (REFORMASI, 2026)
The New Order's economic policy, which relied on foreign investment (PMA) and foreign debt (IGGI), paradoxically engendered dependency, sharp socio-economic inequality, and the marginalization of domestic enterprises, despite its success in curbing inflation. This research aims to analyze the historical significance of the 1974 Malari Incident as the culmination of public unrest spearheaded by students. Employing Kuntowijoyo's historical research method, this study examines primary sources, such as archives and contemporary news reports, as well as secondary literature. The findings reveal how discontent over the impacts of development was successfully consolidated by figures like Hariman Siregar, transforming sporadic actions into a solid mass movement. This movement raised the central issues of the dominance of foreign capital, particularly from Japan, and the controversial role of the presidential Personal Assistants (Aspri). In conclusion, the fundamental significance of the Malari Incident transcends that of a momentary political protest. The event reaffirms the historical thesis that national consciousness and responsibility are a calling for every intellectual, regardless of their academic discipline a principle reflected by medical and engineering students during the national movement era. They are called to "diagnose" and "treat" societal ills, such as injustice, thereby proving the essential role of students as a moral and intellectual force within Indonesia's political landscape.Kebijakan ekonomi Orde Baru yang bertumpu pada modal asing (PMA) dan utang luar negeri (IGGI), meski berhasil menekan inflasi, secara paradoksal justru melahirkan ketergantungan, ketimpangan sosial-ekonomi tajam, dan marginalisasi usaha domestik. Penelitian ini bertujuan menganalisis signifikansi historis Peristiwa Malari 1974 sebagai puncak artikulasi keresahan publik yang dimotori oleh mahasiswa. Dengan menggunakan metode penelitian sejarah Kuntowijoyo, kajian ini mengkaji sumber primer berupa arsip dan berita sezaman serta literatur sekunder. Hasil penelitian menunjukkan bagaimana kekecewaan atas dampak pembangunan berhasil dikonsolidasikan oleh figur seperti Hariman Siregar dari berbagai aksi sporadis menjadi gerakan massa yang solid. Gerakan ini mengangkat isu sentral tentang dominasi modal asing, khususnya Jepang, dan peran kontroversial Asisten Pribadi (Aspri) presiden. Simpulannya, signifikansi fundamental Malari melampaui gugatan politik sesaat. Peristiwa ini menegaskan kembali tesis historis bahwa kesadaran dan tanggung jawab kebangsaan adalah panggilan bagi setiap kaum terpelajar, tanpa tersekat disiplin ilmu—sebagaimana tercermin pada para mahasiswa kedokteran dan teknik di era pergerakan nasional. Mereka terpanggil untuk "mendiagnosis" dan "mengobati" penyakit masyarakat seperti ketidakadilan, membuktikan peran esensial mahasiswa sebagai kekuatan moral dan intelektual dalam lanskap politik Indonesia.